2016
DOI: 10.1021/acschembio.6b00074
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Adaption May Explain the Slow Dissociation Kinetics of Roniciclib (BAY 1000394), a Type I CDK Inhibitor with Kinetic Selectivity for CDK2 and CDK9

Abstract: Roniciclib (BAY 1000394) is a type I pan-CDK (cyclin-dependent kinase) inhibitor which has revealed potent efficacy in xenograft cancer models. Here, we show that roniciclib displays prolonged residence times on CDK2 and CDK9, whereas residence times on other CDKs are transient, thus giving rise to a kinetic selectivity of roniciclib. Surprisingly, variation of the substituent at the 5-position of the pyrimidine scaffold results in changes of up to 3 orders of magnitude of the drug-target residence time. CDK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 54 publications
1
52
0
2
Order By: Relevance
“…However, thermodynamic selectivity may not map with kinetic selectivity, and indeed as noted above, kinetic selectivity can still exist even in the absence of thermodynamic selectivity. 21,23,3841 …”
Section: Kinetic Selectivitymentioning
confidence: 99%
“…However, thermodynamic selectivity may not map with kinetic selectivity, and indeed as noted above, kinetic selectivity can still exist even in the absence of thermodynamic selectivity. 21,23,3841 …”
Section: Kinetic Selectivitymentioning
confidence: 99%
“…[4] Indeed, more recent studies attributed the slow binding kinetics to efficient hydrophobic contacts rather than the kinetic dissociation barrier introduced by the DFG-out transition. [8] In some cases,t he presence of water-shielded hydrogen bonds can also lead to slow dissociation. [6] In addition to protein conformational changes,t he rearrangement of water molecules has been discussed as apotential mechanism influencing inhibitor residence time.…”
mentioning
confidence: 99%
“…[12] Ar ecent survey of the PDB archive for halogen-protein interactions reported that 33 %ofall non-bonded interactions (excluding C À X···H contacts) of the heavier halogens in the protein database form aromatic stacking interactions of the C À X···p type. strated for the CDK inhibitor roniciclib, [8] and it is likely that halogen atoms also contribute to the very slow off-rates observed for the ERK inhibitor VTX-11e. The effect of gatekeeper mutation on the binding kinetics of haspin with tubercidin derivatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in accordance with a sustained inhibitory effect on retinoblastoma protein phosphorylation, indicating that the target RT on CDK2 may contribute to sustained target engagement and antitumor efficacy. 9 Importantly, kinetic selectivity can only occur when a drug's RT outlasts its PK profile.…”
mentioning
confidence: 99%